Answer:
The answer is 61.
Step-by-step explanation:
Let, the numbers are: x, (x+2), (x+4)
Now, x+x+2+x+4 = 183
3x + 6 = 183
3x = 177
x = 59
So, second number would be: (x+2) = (59+2) = 61
Answer:
0.03 more flour per cupcake
Step-by-step explanation:
3.12/8 = 0.39
2.52/7 = 0.36
0.39 - 0.36 = 0.03
Hope this helps c:
Answer:
-91w + 60
Step-by-step explanation:
to simplify this -10(10w-6-w)-w
we have,
-10(10w-6-w)-w
-100w + 60 + 10w - w
-91w + 60
Answer:
3x + 13y
Explanation:
6x + 8y − (3x − 5y)
Distribute the Negative Sign
6x + 8y + −1(3x − 5y)
6x + 8y + −1(3x) + −1(−5y)
6x + 8y + −3x + 5y
Combine Like Terms
6x + 8y + −3x + 5y
(6x + −3x) + (8y + 5y)
= 3x + 13y
Answer:
simplify the expression: 6x+5y
Step-by-step explanation: